Composition for transmission belt and application thereof

The transmission belt composition addresses the issue of inadequate adhesion in conventional rubber compositions by using a specific combination of ethylene α-olefin-non-conjugated polyene copolymer, zinc oxide, and sulfur compound crosslinker, resulting in enhanced adhesion and improved belt performance.

JP2025075455APending Publication Date: 2025-05-15MITSUI CHEMICALS INC

Patent Information

Application Number
JP2023186632
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-31
Publication Date
2025-05-15

AI Technical Summary

Technical Problem

Conventional rubber compositions used in wrap belts exhibit inadequate adhesion to the diene rubber core material, necessitating an improvement in adhesion properties.

Method used

A composition for a transmission belt is developed, incorporating an ethylene α-olefin-non-conjugated polyene copolymer, zinc oxide, cyclohexylamine salts of 2-mercaptobenzothiazole, and a sulfur compound crosslinker, which enhances adhesion to the core material.

Benefits of technology

The transmission belt composition achieves excellent adhesion to the core material, improving the overall performance and durability of the belt.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025075455000001
    Figure 2025075455000001
  • Figure 2025075455000002
    Figure 2025075455000002
  • Figure 2025075455000003
    Figure 2025075455000003
Patent Text Reader

Abstract

To provide a composition for a transmission belt having excellent adhesiveness to a core material.SOLUTION: There is provided a composition for a transmission belt which comprises (B) a copolymer containing a structural unit [b1] derived from ethylene, a structural unit [b2] derived from an α-olefin having a carbon number of 3 to 20, a structural unit [b3] derived from a non-conjugated polyene containing only one cyclic olefin structure or vinyl group structure in the molecule and a structural unit [b4] derived from a non-conjugated polyene containing a total of two or more cyclic olefin structures or vinyl group structures in the molecule, (A) a copolymer containing a structural unit [a1] derived from ethylene, a structural unit [a2] derived from an α-olefin having a carbon number of 4 to 20 and a structural unit [a3] derived from a non-conjugated polyene (provided that the copolymer (B) is excluded), (C) zinc oxide, (D) a cyclohexylamine salt of 2-mercaptobenzothiazole and (E) a sulfur compound-based crosslinking agent.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a composition for a power transmission belt and its use. [Background technology]

[0002] 2. Description of the Related Art Power transmission belts are widely used in automobiles, motorcycles, and general industrial machinery as, for example, V-belts such as wrapped belts and raw edge belts, friction power transmission belts such as V-ribbed belts, and meshing power transmission belts such as timing belts.

[0003] Power transmission belts are required to have adhesion, elasticity and abrasion resistance, and chloroprene rubber is generally used to manufacture power transmission belts that satisfy these properties. On the other hand, in order to meet the demands for improved heat resistance and cold resistance, as well as for weight reduction, the use of ethylene-propylene-non-conjugated polyene copolymer rubber instead of chloroprene rubber has been considered (see, for example, Patent Documents 1 and 2). Patent Document 3 describes that a transmission belt with improved wear resistance can be obtained from a rubber composition containing a specific ethylene-α-olefin-non-conjugated polyene copolymer.

[0004] Patent Document 4 describes that a specific ethylene / α-olefin / non-conjugated polyene copolymer having 4 to 20 carbon atoms has an excellent balance of adhesion, processability, and fluidity. Patent Document 5 describes a composition for a transmission belt that contains a specific ethylene / α-olefin / non-conjugated polyene copolymer and zinc oxide. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2001-310951 A [Patent Document 2] JP 2012-215212 A [Patent Document 3] JP 2016-44198 A [Patent Document 4] International Publication No. 2015 / 122415 [Patent Document 5] JP 2021-161358 A Summary of the Invention [Problem to be solved by the invention]

[0006] According to the investigations of the present inventors, there is room for improvement in wrapped belts using conventional rubber compositions from the viewpoint of adhesion to diene rubber constituting the core material. In order to solve the problems in the conventional techniques, an object of the present invention is to provide a composition for a power transmission belt that has excellent adhesion to a core material. [Means for solving the problem]

[0007] The present invention relates to, for example, the following [1] to [4].

[0008] [1] (B) an ethylene-α-olefin-non-conjugated polyene copolymer comprising a structural unit [b1] derived from ethylene, a structural unit [b2] derived from an α-olefin having 3 to 20 carbon atoms, a structural unit [b3] derived from a non-conjugated polyene containing only one partial structure represented by the following general formula (I) or (II) in the molecule, and a structural unit [b4] derived from a non-conjugated polyene containing a total of two or more partial structures represented by the following general formula (I) or (II) in the molecule; (A) an ethylene-α-olefin-non-conjugated polyene copolymer comprising a structural unit [a1] derived from ethylene, a structural unit [a2] derived from an α-olefin having 4 to 20 carbon atoms, and a structural unit [a3] derived from a non-conjugated polyene (excluding the copolymer (B)); (C) zinc oxide, (D) the cyclohexylamine salt of 2-mercaptobenzothiazole, and (E) Sulfur compound-based crosslinking agent A composition for a transmission belt comprising:

[0009] [ka]

[0010] [2] The composition for a transmission belt according to [1], wherein the copolymer (B) satisfies the following requirements (b-1) and (b-2): Requirement (b-1): The molar ratio ([b1] / [b2]) of the structural unit [b1] derived from ethylene to the structural unit [b2] derived from an α-olefin having 3 to 20 carbon atoms is 50 / 50 to 75 / 25. Requirement (b-2): The B value represented by the following formula (ib) is 1.05 or less. B value = [EP] / (2[E]×[P]) (ib) (In formula (ib), [E] and [P] respectively represent the molar fraction of the structural unit [b1] derived from the ethylene and the molar fraction of the structural unit [b2] derived from the α-olefin having 3 to 20 carbon atoms, and [EP] represents the diad chain fraction of ethylene and the α-olefin having 3 to 20 carbon atoms.)

[0011] [3] A laminate including a layer [I] containing the composition for a transmission belt or a cross-linked product thereof according to [1] or [2], and a layer [II] containing a diene rubber or a cross-linked product thereof, which is in contact with the layer [I].

[0012] [4] A power transmission belt comprising the laminate according to [3]. Effect of the Invention

[0013] The composition for a power transmission belt of the present invention has excellent adhesion to a core material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The present invention will now be described in further detail. [Composition for transmission belts] The composition for a power transmission belt of the present invention contains an ethylene-α-olefin-non-conjugated polyene copolymer (A), an ethylene-α-olefin-non-conjugated polyene copolymer (B), zinc oxide (C), a cyclohexylamine salt of 2-mercaptobenzothiazole (D), and a sulfur compound-based crosslinking agent (E), which are described below.

[0015] The composition for a power transmission belt of the present invention contains, as rubber components, an ethylene / α-olefin / non-conjugated polyene copolymer (A) and an ethylene / α-olefin / non-conjugated polyene copolymer (B).

[0016] <Ethylene-α-olefin-non-conjugated polyene copolymer (A)> The ethylene-α-olefin-non-conjugated polyene copolymer (A) (hereinafter also simply referred to as "copolymer (A)") is a copolymer containing a structural unit [a1] derived from ethylene, a structural unit [a2] derived from an α-olefin having 4 to 20 carbon atoms, and a structural unit [a3] derived from a non-conjugated polyene (however, excluding the ethylene-α-olefin-non-conjugated polyene copolymer (B) described later). The α-olefin having 4 to 20 carbon atoms from which the structural unit [a2] is derived is also called the "α-olefin having 4 to 20 carbon atoms [A2]", and the non-conjugated polyene from which the structural unit [a3] is derived is also called the "non-conjugated polyene [A3]".

[0017] 《α-Olefins with 4 to 20 carbon atoms [A2]》 Examples of the α-olefins [A2] having 4 to 20 carbon atoms include linear α-olefins such as 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-nonadecene, and 1-eicosene; and side chain-containing α-olefins such as 4-methyl-1-pentene, 9-methyl-1-decene, 11-methyl-1-dodecene, and 12-ethyl-1-tetradecene. Among these, from the viewpoint of a well-balanced and excellent adhesion and mechanical strength, the α-olefins [A2] having 4 to 20 carbon atoms are preferably α-olefins having 4 to 10 carbon atoms, more preferably 1-butene, 1-hexene, and 1-octene, and even more preferably 1-butene. The α-olefins [A2] having 4 to 20 carbon atoms may be used alone or in combination of two or more kinds.

[0018] Non-conjugated polyenes [A3] Examples of the non-conjugated polyenes [A3] include linear non-conjugated dienes such as 1,4-hexadiene, 1,6-octadiene, 2-methyl-1,5-hexadiene, 6-methyl-1,5-heptadiene, and 7-methyl-1,6-octadiene; cyclohexadiene, dicyclopentadiene, methyltetrahydroindene, 5-vinyl-2-norbornene (VNB), 5-ethylidene-2-norbornene (ENB), 5-methylene-2-norbornene, and 5-isopropylidene. cyclic non-conjugated dienes such as 2,3-diisopropylidene-5-norbornene, 2-ethylidene-3-isopropylidene-5-norbornene, 2-propenyl-2,5-norbornadiene, 1,3,7-octatriene, 1,4,9-decatriene, 4,8-dimethyl-1,4,8-decatriene, and 4-ethylidene-8-methyl-1,7-nonadiene. Among these, from the viewpoint of vulcanization speed, the non-conjugated polyene [A3] is preferably a chain non-conjugated diene such as 1,4-hexadiene, and a cyclic non-conjugated diene such as ENB and VNB, more preferably a cyclic non-conjugated diene, and even more preferably ENB and VNB. The non-conjugated polyene [A3] may be used alone or in combination of two or more kinds.

[0019] Examples of the copolymer (A) include ethylene-1-butene-1,4-hexadiene copolymer, ethylene-1-pentene-1,4-hexadiene copolymer, ethylene-1-hexene-1,4-hexadiene copolymer, ethylene-1-heptene-1,4-hexadiene copolymer, ethylene-1-octene-1,4-hexadiene copolymer, ethylene-1-nonene-1,4-hexadiene copolymer, ethylene-1-decene-1,4-hexadiene copolymer, ethylene-1-butene ethylene-1-octene-1,4-hexadiene copolymer, ethylene-1-butene-5-ethylidene-2-norbornene (ENB) copolymer, ethylene-1-pentene-ENB copolymer, ethylene-1-hexene-ENB copolymer, ethylene-1-heptene-ENB copolymer, ethylene-1-octene-ENB copolymer, ethylene-1-nonene-ENB copolymer, ethylene-1-decene-ENB copolymer, and ethylene-1-butene-1-octene-ENB copolymer. Among these, ethylene-1-butene-ENB copolymer is preferable from the viewpoint of mechanical strength.

[0020] The copolymer (A) may contain structural units derived from at least one or more biomass-derived monomers (biomass-derived ethylene [A1], an α-olefin having 4 to 20 carbon atoms [A2], and a non-conjugated polyene [A3]).

[0021] Requirements (a-1) to (a-4') The copolymer (A) preferably satisfies one or more of the following requirements (a-1) to (a-3), more preferably satisfies two or more of the following requirements (a-1) to (a-3), and further preferably satisfies all of the following requirements (a-1) to (a-3). In one embodiment, the copolymer (A) preferably satisfies one or more of the following requirements (a-4) to (a-4'), and more preferably satisfies all of the following requirements (a-4) to (a-4').

[0022] Requirement (a-1): The molar ratio ([a1] / [a2]) of the structural unit [a1] derived from ethylene to the structural unit [a2] derived from an α-olefin having 4 to 20 carbon atoms is 40 / 60 to 90 / 10. The copolymer (A) having a molar ratio within the above range has an excellent balance between rubber elasticity at low temperatures and tensile strength at room temperature. The lower limit of the molar ratio ([a1] / [a2]) is preferably 45 / 55, more preferably 50 / 50, even more preferably 55 / 45, still more preferably 60 / 40, and particularly preferably 65 / 35. The upper limit of the molar ratio ([a1] / [a2]) is preferably 80 / 20, and more preferably 75 / 25.

[0023] Requirement (a-2): The content of the structural unit [a3] derived from a non-conjugated polyene is 0.1 to 6.0 mol % relative to 100 mol % of the total of the structural units [a1], [a2] and [a3]. The copolymer (A) having the content of the structural unit [a3] within the above range has sufficient crosslinkability and flexibility. The lower limit of the content of the structural unit [a3] is preferably 0.5 mol %, and the upper limit of the content of the structural unit [a3] is preferably 4.0 mol %, more preferably 3.5 mol %, and further preferably 3.0 mol %. The contents of the structural unit [a1], the structural unit [a2] and the structural unit [a3] are 1 It can be determined by intensity measurement using a H-NMR spectrometer.

[0024] Requirement (a-3): The B value represented by the following formula (ia) is 1.20 or more. B value=([EB]+2[Y]) / [2×[E]×([B]+[Y])]···(ia) (In formula (ia), [E], [B] and [Y] respectively represent the molar fraction of the structural unit [a1] derived from ethylene, the molar fraction of the structural unit [a2] derived from an α-olefin having 4 to 20 carbon atoms and the molar fraction of the structural unit [a3] derived from a non-conjugated polyene, and [EB] represents the ethylene-α-olefin dyad chain fraction having 4 to 20 carbon atoms.) The B value is preferably 1.20 to 1.80, and more preferably 1.22 to 1.40.

[0025] The copolymer (A) satisfying the requirement (a-3) has a high degree of alternation of the monomer units constituting the copolymer and a low degree of crystallinity, and therefore the processability of the resulting composition is improved. The B value is an index showing the randomness of the distribution of copolymerized monomer sequences in a copolymer, and [E], [B], [Y] and [EB] in the formula (ia) are 13 The amount of carbon ions can be determined by measuring the C-NMR spectrum, based on the reports of JC Randal [Macromolecules, 15, 353 (1982)] and J. Ray [Macromolecules, 10, 773 (1977)].

[0026] Requirement (a-4): Mooney viscosity ML(1+4) 100°C is 5 to 150. The Mooney viscosity ML(1+4)100°C is preferably 5 to 100, more preferably 10 to 90, and further preferably 20 to 85. The copolymer (A) having the Mooney viscosity ML(1+4)100°C in the above range has good processability and flowability, and also exhibits good post-treatment quality (ribbon handleability) and has excellent rubber physical properties.

[0027] Requirement (a-4'): Mooney viscosity ML(1+4) at 125°C is 3 to 100. The Mooney viscosity ML(1+4)125°C is preferably 3 to 70, more preferably 10 to 65, and further preferably 20 to 60. The copolymer (A) having the Mooney viscosity ML(1+4)125°C within the above range has good processability and flowability, and also exhibits good post-treatment quality (ribbon handleability) and has excellent rubber physical properties.

[0028] The composition for a transmission belt may contain one type of copolymer (A) or may contain two or more types of copolymers (A). Copolymer (A) generally has higher adhesion than ethylene-propylene-non-conjugated polyene copolymers contained in conventional rubber compositions. Therefore, in the composition for a transmission belt containing copolymer (A), the bonding between the compounded components is strong, and the belt processability and moldability are excellent.

[0029] <<Method for producing copolymer (A)>> The copolymer (A) can be obtained by a conventionally known production method using a metallocene catalyst. For example, examples of the metallocene catalyst and the production method using the catalyst are described in International Publication No. 2015 / 122415, particularly in paragraphs

[0249] to

[0320] of the publication.

[0030] <Ethylene-α-olefin-non-conjugated polyene copolymer (B)> The ethylene-α-olefin-non-conjugated polyene copolymer (B) (hereinafter also simply referred to as "copolymer (B)") contains a structural unit [b1] derived from ethylene, a structural unit [b2] derived from an α-olefin having 3 to 20 carbon atoms, a structural unit [b3] derived from a non-conjugated polyene containing only one partial structure represented by the following general formula (I) or (II) in the molecule, and a structural unit [b4] derived from a non-conjugated polyene containing a total of two or more partial structures represented by the following general formula (I) or (II) in the molecule. The α-olefin having 3 to 20 carbon atoms that derives the structural unit [b2] is also called the "α-olefin having 3 to 20 carbon atoms [B2]", the non-conjugated polyene that derives the structural unit [b3] is also called the "non-conjugated polyene [B3]", and the non-conjugated polyene that derives the structural unit [b4] is also called the "non-conjugated polyene [B4]".

[0031] [ka]

[0032] 《α-Olefins with 3 to 20 carbon atoms [B2]》 Examples of the α-olefins [B2] having 3 to 20 carbon atoms include propylene, 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-heptene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, and 1-eicosene. Among these, the α-olefins [B2] having 3 to 20 carbon atoms are preferably α-olefins having 3 to 8 carbon atoms such as propylene, 1-butene, 1-hexene, and 1-octene, and more preferably propylene, because they have good mechanical strength. These α-olefins may be used alone or in combination of two or more.

[0033] Non-conjugated polyene [B3] The non-conjugated polyene [B3] is a non-conjugated polyene having one partial structure represented by the general formula (I) in the molecule and no partial structure represented by the general formula (II) in the molecule, or a non-conjugated polyene having one partial structure represented by the general formula (II) in the molecule and no partial structure represented by the general formula (I) in the molecule.

[0034] The partial structure represented by the general formula (I) is a partial structure of a cyclic olefin, that is, the partial structure represented by the general formula (I) is a structure consisting of an atomic group including two adjacent carbon atoms constituting a ring of a cyclic olefin and connected by a double bond, and two hydrogen atoms each bonded to the two carbon atoms.

[0035] For example, 5-ethylidene-2-norbornene (ENB) contains one partial structure represented by the general formula (I) in one molecule, and therefore corresponds to the non-conjugated polyene [B3]. Meanwhile, dicyclopentadiene (DCPD) contains two partial structures represented by the general formula (I) in one molecule, and therefore corresponds to the non-conjugated polyene [B4] described below. 5-vinylidene-2-norbornene (VNB) contains one partial structure represented by the general formula (I) in one molecule and one partial structure represented by the general formula (II) in one molecule, and therefore corresponds to the non-conjugated polyene [B4] described below.

[0036] Examples of the non-conjugated polyene [B3] include the following aliphatic polyenes and alicyclic polyenes. Examples of the aliphatic polyenes include 1,4-hexadiene, 1,5-heptadiene, 1,6-octadiene, 1,7-nonadiene, 1,8-decadiene, 1,12-tetradecadiene, 3-methyl-1,4-hexadiene, 4-methyl-1,4-hexadiene, 5-methyl-1,4-hexadiene, 4-ethyl-1,4-hexadiene, 3,3-dimethyl-1,4-hexadiene, 5-methyl-1,4-heptadiene, 5-ethyl-1,4-heptadiene, 5-methyl-1,5-heptadiene, 6-methyl-1,5-heptadiene, 5-ethyl-1,5 -heptadiene, 4-methyl-1,4-octadiene, 5-methyl-1,4-octadiene, 4-ethyl-1,4-octadiene, 5-ethyl-1,4-octadiene, 5-methyl-1,5-octadiene, 6-methyl-1,5-octadiene, 5-ethyl-1,5-octadiene, 6-ethyl-1,5-octadiene, 6-methyl-1,6-octadiene, 7-methyl-1,6-octadiene, 6-ethyl-1,6-octadiene, 6-propyl-1,6-octadiene, 6-butyl-1,6-octadiene, 4-methyl-1,4-nonadiene, 5-methyl ethyl-1,4-nonadiene, 4-ethyl-1,4-nonadiene, 5-ethyl-1,4-nonadiene, 5-methyl-1,5-nonadiene, 6-methyl-1,5-nonadiene, 5-ethyl-1,5-nonadiene, 6-ethyl-1,5-nonadiene, 6-methyl-1,6-nonadiene, 7-methyl-1,6-nonadiene, 6-ethyl-1,6-nonadiene, 7-ethyl-1,6-nonadiene, 7-methyl-1,7-nonadiene, 8-methyl-1,7-nonadiene, 7-ethyl-1,7-nonadiene, 5-methyl-1,4-decadiene, 5-ethyl-1,4-decadiene , 5-methyl-1,5-decadiene, 6-methyl-1,5-decadiene, 5-ethyl-1,5-decadiene, 6-ethyl-1,5-decadiene, 6-methyl-1,6-decadiene, 6-ethyl-1,6-decadiene, 7-methyl-1,6-decadiene, 7-ethyl-1,6-decadiene, 7-methyl-1,7-decadiene, 8-methyl-1,7-decadiene, 7-ethyl-1,7-decadiene, 8-ethyl-1,7-decadiene, 8-methyl-1,8-decadiene, 9-methyl-1,8-decadiene, 8-ethyl-1,8-decadiene, 6-methyl-1,Examples of the aliphatic polyene include 6-undecadiene and 9-methyl-1,8-undecadiene, and among these, 7-methyl-1,6-octadiene is preferred. These aliphatic polyenes may be used alone or in combination of two or more.

[0037] Examples of the alicyclic polyene include polyenes composed of an alicyclic portion having one carbon-carbon double bond (unsaturated bond) and a chain portion (ethylidene, propylidene, etc.) bonded to the carbon atom constituting the alicyclic portion by a carbon-carbon double bond. Examples of the alicyclic polyene include 5-ethylidene-2-norbornene (ENB), 5-propylidene-2-norbornene, 5-butylidene-2-norbornene, 2-methyl-2,5-norbornadiene, and 2-ethyl-2,5-norbornadiene. As the alicyclic polyene, ENB is preferable.

[0038] Non-conjugated polyenes [B4] The non-conjugated polyene [B4] is a non-conjugated polyene containing two or more partial structures represented by the general formula (I) in the molecule and not containing any partial structure represented by the general formula (II) in the molecule, a non-conjugated polyene containing two or more partial structures represented by the general formula (II) in the molecule and not containing any partial structure represented by the general formula (I) in the molecule, or a non-conjugated polyene containing one or more partial structures represented by the general formula (I) in the molecule and not containing any partial structure represented by the general formula (II) in the molecule.

[0039] Examples of the non-conjugated polyenes [B4] include alicyclic polyenes having an alicyclic portion with a carbon-carbon double bond (unsaturated bond) and a chain portion bonded to a carbon atom constituting the alicyclic portion and containing a vinyl group, and aliphatic polyenes having vinyl groups at both ends of the molecule. Examples of the non-conjugated polyenes [B4] include 5-alkenyl-2-norbornenes such as 5-vinyl-2-norbornene (VNB) and 5-allyl-2-norbornene; 2,5-norbornadiene, dicyclopentadiene (DCPD) and tetracyclo[6.2.1.1 3,6 .0 2,7] Alicyclic polyenes such as dodeca-4,9-diene; and aliphatic polyenes such as α,ω-dienes such as 1,7-octadiene and 1,9-decadiene. These may be used alone or in combination of two or more.

[0040] As the non-conjugated polyene [B4], 5-vinyl-2-norbornene (VNB), 5-alkenyl-2-norbornene, dicyclopentadiene, 2,5-norbornadiene, 1,7-octadiene and 1,9-decadiene are preferred, with VNB being particularly preferred.

[0041] The copolymer (B) may contain structural units derived from at least one or more biomass-derived monomers (biomass-derived ethylene [B1], α-olefins having 4 to 20 carbon atoms [B2], non-conjugated polyenes [B3], and non-conjugated polyenes [B4]).

[0042] 《Requirements (b-1)~(b-4)》 The copolymer (B) preferably satisfies any one of the following requirements (b-1) to (b-4), and more preferably satisfies the following requirements (b-1) and (b-2).

[0043] Requirement (b-1): The molar ratio ([b1] / [b2]) of the structural unit [b1] derived from ethylene to the structural unit [b2] derived from an α-olefin having 3 to 20 carbon atoms is 50 / 50 to 75 / 25. The molar ratio ([b1] / [b2]) is preferably 50 / 50 to 70 / 30, more preferably 55 / 45 to 65 / 35, and further preferably 55 / 45 to 60 / 40.

[0044] Requirement (b-2): The B value represented by the following formula (ib) is 1.05 or less. B value = [EP] / (2[E]×[P]) (ib) (In formula (ib), [E] and [P] respectively represent the molar fraction of the structural unit [b1] derived from ethylene and the molar fraction of the structural unit [b2] derived from an α-olefin having 3 to 20 carbon atoms, and [EP] represents the dyad chain fraction of ethylene and an α-olefin having 3 to 20 carbon atoms.)

[0045] The B value is an index showing the randomness of the distribution of copolymerized monomer sequences in a copolymer, and [E], [P] and [EP] in the formula (ib) are 13 The amount of carbon ions can be determined by measuring the C-NMR spectrum, based on the reports of JC Randal [Macromolecules, 15, 353 (1982)] and J. Ray [Macromolecules, 10, 773 (1977)]. The B value of 1.0 indicates that the copolymer has the highest randomness, and the smaller the B value, the higher the blockiness of the copolymer, and conversely, the higher the B value, the higher the alternation of the copolymer. It is preferable that the B value is within the above range in that the copolymer (B) has excellent blocking resistance.Furthermore, it is preferable that the B value is closer to 1.0 in that the copolymer (B) has excellent randomness and exhibits excellent low-temperature properties.

[0046] As the copolymer (B), an ethylene-propylene-5-ethylidene-2-norbornene (ENB)-5-vinyl-2-norbornene (VNB) copolymer is particularly preferred. The copolymer (B) can be produced by a conventionally known method, for example, the method described in

[0057] to

[0102] of JP2014-208740A.

[0047] Requirement (b-3): The molar ratio of the structural unit [b3] to the structural unit [b4] ([b3] / [b4]) is 85 / 15 to 99.5 / 0.5. The molar ratio ([b3] / [b4]) is preferably from 90 / 10 to 99.5 / 0.5, and more preferably from 95 / 5 to 99.5 / 0.5.

[0048] Requirement (b-4): The total content of the structural units [b3] and [b4] is 0.5 to 6.0 mol % relative to 100 mol % of all structural units contained in the copolymer (B). The total content of the structural unit [b3] and the structural unit [b4] is preferably 1.0 to 6.0 mol%, more preferably 2.0 to 5.0 mol%. When the content is within the above range, it is preferable from the viewpoint of the rubber-like properties (e.g., permanent elongation and compression set) of the copolymer (B).

[0049] The content of each of the structural units [b1], [b2], [b3] and [b4] is: 1 It can be determined by intensity measurement using a H-NMR spectrometer.

[0050] The total content of the copolymer (A) and the copolymer (B) in the composition for the power transmission belt is usually 20% by mass or more, preferably 25 to 90% by mass, more preferably 30 to 70% by mass, and further preferably 35 to 50% by mass. The mass ratio of copolymer (A) to copolymer (B) (copolymer (A) / copolymer (B)) is preferably 95 / 5 to 50 / 50, more preferably 90 / 10 to 60 / 40, further preferably 90 / 10 to 70 / 30, and particularly preferably 90 / 10 to 80 / 20.

[0051] <Zinc oxide (C)> The composition for a power transmission belt according to the present invention contains zinc oxide (C). Examples of zinc oxide (C) include those commercially available under the names of zinc oxide, zinc white, activated zinc white, composite zinc white, surface-treated zinc white, and composite activated zinc white, which are classified into types 1, 2, and 3 according to JIS K 1410 (2006). Commercially available zinc oxide (C) includes, for example, zinc oxide type 2 (JIS K 1410 (2006)) (e.g., "ZnO#1" manufactured by Hakusui Tech Co., Ltd.) and activated zinc white (e.g., "META-Z 102" (trade name; manufactured by Inoue Seki Kogyo Co., Ltd.)). In the present invention, active zinc white refers to zinc oxide having a specific surface area of ​​10 to 80 m 2 / g and has an average particle size of 0.05 to 20 μm as measured by laser diffraction method.

[0052] Zinc oxide (C) acts as a vulcanization accelerator during molding, and when fatty acid is present, it forms a complex with it to increase the activity of the vulcanization accelerator and improve the vulcanization rate. Zinc oxide (C) also acts as a weighting agent. Zinc oxide (C) may be used alone or in combination of two or more types.

[0053] The content of zinc oxide (C) in the composition for a transmission belt is preferably 0.2 to 15 parts by mass, more preferably 0.5 to 10 parts by mass, and further preferably 1 to 8 parts by mass, per 100 parts by mass of the total of the copolymers (A) and (B).

[0054] <Cyclohexylamine salt of 2-mercaptobenzothiazole (D)> The composition for a power transmission belt according to the present invention contains a cyclohexylamine salt of 2-mercaptobenzothiazole (D). When the composition for a transmission belt contains the cyclohexylamine salt of 2-mercaptobenzothiazole (D), the adhesion between the composition for a transmission belt and a core material is excellent.

[0055] The cyclohexylamine salt of 2-mercaptobenzothiazole (D) usually acts as a vulcanization accelerator. Commercially available products of the cyclohexylamine salt of 2-mercaptobenzothiazole (D) include, for example, Suncerer HM (trade name; manufactured by Sanshin Chemical Industry Co., Ltd.) and Noccelaer M-60-OT (trade name; manufactured by Ouchi Shinko Chemical Industry Co., Ltd.).

[0056] The content of the cyclohexylamine salt of 2-mercaptobenzothiazole (D) in the composition for power transmission belt is usually 0.1 to 20 parts by mass, preferably 0.5 to 10 parts by mass, more preferably 1 to 5 parts by mass, further preferably 1 to 3 parts by mass, and particularly preferably 1 to 2 parts by mass, based on 100 parts by mass in total of the copolymers (A) and (B). When the content of the cyclohexylamine salt of 2-mercaptobenzothiazole (D) is within the above range, the composition for power transmission belt is preferred because it has excellent adhesion to the core material.

[0057] <Sulfur compound-based crosslinking agent (E)> The composition for a power transmission belt according to the present invention contains a sulfur compound-based crosslinking agent (E).

[0058] Examples of the sulfur compound-based crosslinking agent (E) include sulfur, sulfur chloride, sulfur dichloride, morpholine disulfide, alkylphenol disulfide, tetramethylthiuram disulfide, and selenium dithiocarbamate.

[0059] The content of the sulfur compound-based crosslinking agent (E) in the composition for a transmission belt is usually 0.3 to 10 parts by mass, preferably 0.5 to 7.0 parts by mass, more preferably 0.7 to 5.0 parts by mass, and even more preferably 1.0 to 3.0 parts by mass, relative to 100 parts by mass in total of the copolymers (A) and (B). The sulfur compound-based crosslinking agent (E) may be used alone or in combination of two or more.

[0060] <Other ingredients> In addition to the above-mentioned components, the composition for the transmission belt may further contain at least one selected from a softener, an inorganic filler (reinforcing agent), an antioxidant, a processing aid, an activator, a moisture absorbent, an antistatic agent, a colorant, a lubricant, and a thickener, within a range that does not impair the effects of the present invention. The composition for the transmission belt may further contain a polymer other than the copolymer (A) and the copolymer (B), such as an elastomer and / or a rubber, within a range that does not impair the effects of the present invention. Each of the components described below may be used alone or in combination of two or more kinds.

[0061] The composition for the transmission belt may contain a crosslinking agent other than the sulfur compound-based crosslinking agent (E) (hereinafter, also referred to as "other crosslinking agent"). Examples of the other crosslinking agent include organic peroxides, phenolic resins, hydrosilicone compounds, amino resins, quinones or derivatives thereof, amine compounds, azo compounds, epoxy compounds, and isocyanate compounds. Among these, organic peroxides are preferred as the other crosslinking agent.

[0062] Examples of the organic peroxide include dicumyl peroxide, di-tert-butyl peroxide, 2,5-di-(tert-butylperoxy)hexane, 2,5-dimethyl-2,5-di-(tert-butylperoxy)hexane, 2,5-dimethyl-2,5-di-(tert-butylperoxy)hexyne-3, 1,3-bis(tert-butylperoxyisopropyl)benzene, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, n-butyl-4,4-bis(tert-butylperoxy)valerate, benzoyl peroxide, p-chlorobenzoyl peroxide, 2,4-dichlorobenzoyl peroxide, tert-butyl peroxybenzoate, tert-butylperoxyisopropyl carbonate, diacetyl peroxide, lauroyl peroxide, and tert-butylcumyl peroxide.

[0063] When an organic peroxide is used as another crosslinking agent, the content of the organic peroxide is usually 0.1 to 20 parts by mass, preferably 0.2 to 15 parts by mass, and more preferably 0.5 to 10 parts by mass, per 100 parts by mass of the total of the copolymer (A) and the copolymer (B).

[0064] When an organic peroxide is used as another crosslinking agent, it is preferable to use a crosslinking assistant in combination. Examples of the crosslinking assistant include quinone dioxime crosslinking assistant such as p-quinone dioxime, acrylic crosslinking assistant such as ethylene glycol dimethacrylate and trimethylolpropane trimethacrylate, allyl crosslinking assistant such as diallyl phthalate and triallyl isocyanurate, maleimide crosslinking assistant, divinylbenzene, and metal oxide such as magnesium oxide.

[0065] When the composition for a transmission belt contains a crosslinking auxiliary, the content of the crosslinking auxiliary is usually 0.5 to 10 mol, preferably 0.5 to 7 mol, and more preferably 1 to 5 mol, per 1 mol of the organic peroxide.

[0066] The composition for a power transmission belt may contain a vulcanization accelerator other than the cyclohexylamine salt of 2-mercaptobenzothiazole (D) (hereinafter, also referred to as "other vulcanization accelerator").

[0067] Other vulcanization accelerators include, for example, sulfenamide-based vulcanization accelerators such as N-cyclohexyl-2-benzothiazole sulfenamide (for example, Suncerer CM (trade name; manufactured by Sanshin Chemical Industry Co., Ltd.)), N-oxydiethylene-2-benzothiazole sulfenamide, and N,N'-diisopropyl-2-benzothiazole sulfenamide; Thiazole vulcanization accelerators such as 2-mercaptobenzothiazole, 2-(4-morpholinodithio)benzothiazole, 2-(2,4-dinitrophenyl)mercaptobenzothiazole, 2-(2,6-diethyl-4-morpholinothio)benzothiazole, and dibenzothiazyl disulfide; Guanidine vulcanization accelerators such as diphenylguanidine, triphenylguanidine, and diorthotolylguanidine; Aldehyde-amine vulcanization accelerators such as acetaldehyde-aniline condensation products and butyraldehyde-aniline condensation products; Imidazoline-based vulcanization accelerators such as 2-mercaptoimidazoline; Thiourea vulcanization accelerators such as diethylthiourea and dibutylthiourea; thiuram-based vulcanization accelerators such as tetramethylthiuram monosulfide, tetramethylthiuram disulfide (for example, Suncerer TT (trade name; manufactured by Sanshin Chemical Industry Co., Ltd.)), tetraethylthiuram disulfide, tetrabutylthiuram disulfide, and dipentamethylenethiuram tetrasulfide; dithioacid salt vulcanization accelerators such as zinc dimethyldithiocarbamate, zinc diethyldithiocarbamate, zinc dibutyldithiocarbamate (for example, Suncerer BZ (trade name; manufactured by Sanshin Chemical Industry Co., Ltd.)), and tellurium diethyldithiocarbamate; thiourea-based vulcanization accelerators such as ethylene thiourea (for example, Sancerer 22C (trade name; manufactured by Sanshin Chemical Industry Co., Ltd.)), N,N'-diethyl thiourea, and N,N'-dibutyl thiourea; xanthate-based vulcanization accelerators such as zinc dibutylxantogenate; Examples include:

[0068] When the composition for a transmission belt contains other vulcanization accelerators, the total content of the cyclohexylamine salt of 2-mercaptobenzothiazole (D) and the other vulcanization accelerators is usually 0.1 to 20 parts by mass, preferably 0.2 to 15 parts by mass, and more preferably 0.5 to 10 parts by mass, per 100 parts by mass of the total of the copolymer (A) and the copolymer (B). In the case where the composition for a transmission belt contains other vulcanization accelerators, the mass ratio of the cyclohexylamine salt of 2-mercaptobenzothiazole (D) to the other vulcanization accelerators (cyclohexylamine salt of 2-mercaptobenzothiazole (D) / other vulcanization accelerators) is preferably 25 / 75 to 75 / 25, more preferably 30 / 70 to 70 / 30, further preferably 35 / 65 to 60 / 40, and particularly preferably 40 / 60 to 50 / 50.

[0069] Since the composition for a transmission belt contains the sulfur compound-based crosslinking agent (E), it is also preferable to use a vulcanization aid, such as magnesium oxide. When the composition for a transmission belt contains a vulcanization aid, the content of the vulcanization aid is usually 1 to 20 parts by mass per 100 parts by mass of the total of the copolymer (A) and the copolymer (B).

[0070] Softener Examples of the softener include: Petroleum-based softeners such as process oil, lubricating oil, paraffin oil, liquid paraffin, petroleum asphalt and Vaseline; Coal tar-based softeners such as coal tar; Fatty oil-based softeners such as castor oil, linseed oil, rapeseed oil, soybean oil and coconut oil; Waxes such as beeswax and carnauba wax; fatty acids or salts thereof, such as ricinoleic acid, palmitic acid, stearic acid, barium stearate and calcium stearate; Naphthenic acid, pine oil, rosin or its derivatives; Synthetic polymeric substances such as terpene resins, petroleum resins and coumarone-indene resins; Ester-based softeners such as dioctyl phthalate and dioctyl adipate; Other examples include microcrystalline wax, liquid polybutadiene, modified liquid polybutadiene, hydrocarbon-based synthetic lubricating oil, tall oil, and sub(factice). As the softener, a petroleum-based softener is preferable, and process oil is more preferable.

[0071] When the composition for a transmission belt contains a softener, the content of the softener is usually 2 to 100 parts by mass, preferably 5 to 100 parts by mass, more preferably 20 to 60 parts by mass, and further preferably 30 to 50 parts by mass, per 100 parts by mass in total of the copolymer (A) and the copolymer (B).

[0072] {Inorganic filler (reinforcing material)} Examples of inorganic fillers (reinforcing materials) include calcium carbonate (e.g., light calcium carbonate, heavy calcium carbonate, and activated calcium carbonate), talc (e.g., fine talc), clay, silica, fine silicic acid, and carbon black. Among these, carbon black is preferred as the inorganic filler (reinforcing material).

[0073] When the composition for a transmission belt contains an inorganic filler, the content of the inorganic filler is usually 0.1 to 200 parts by mass, preferably 10 to 200 parts by mass, more preferably 30 to 150 parts by mass, further preferably 50 to 120 parts by mass, and particularly preferably 70 to 90 parts by mass, per 100 parts by mass in total of the copolymer (A) and the copolymer (B).

[0074] 《Anti-aging agent (stabilizer)》 The composition for a power transmission belt contains an antioxidant (stabilizer), which can extend the life of a (crosslinked) molded article formed from the composition for a power transmission belt. Examples of the antioxidant include amine-based antioxidants, amine-ketone-based antioxidants, phenol-based antioxidants, and sulfur-based antioxidants.

[0075] Examples of the amine-based antioxidant include aromatic secondary amine-based antioxidants such as phenylbutylamine and N,N-di-2-naphthyl-p-phenylenediamine. An example of the amine-ketone antioxidant is 2,2,4-trimethyl-1,2-dihydroquinoline (for example, Nocrac 224 (trade name; manufactured by Ouchi Shinko Chemical Industry Co., Ltd.)). Examples of phenol-based antioxidants include dibutylhydroxytoluene and pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate].

[0076] Examples of sulfur-based anti-aging agents include thioether-based anti-aging agents such as bis[2-methyl-4-(3-n-alkylthiopropionyloxy)-5-t-butylphenyl]sulfide; dithiocarbamate-based anti-aging agents such as nickel dibutyldithiocarbamate; 2-mercaptobenzoylimidazole, 2-mercaptobenzimidazole (for example, Sandant MB (trade name; manufactured by Sanshin Chemical Industry Co., Ltd.)), zinc salt of 2-mercaptobenzimidazole, dilaurylthiodipropionate, and distearylthiodipropionate.

[0077] When the composition for a transmission belt contains an antioxidant, the content of the antioxidant is usually 0.3 to 10 parts by mass, preferably 0.5 to 7.0 parts by mass, more preferably 1.0 to 6.0 parts by mass, further preferably 2.0 to 5.0 parts by mass, and particularly preferably 3.0 to 5.0 parts by mass, per 100 parts by mass of the total of the copolymer (A) and the copolymer (B).

[0078] Processing aids As the processing aid, a wide variety of processing aids that are generally compounded with rubber can be used. Examples of processing aids include ricinoleic acid, stearic acid, palmitic acid, lauric acid, barium stearate, zinc stearate, calcium stearate, and esters. Among these, stearic acid is preferred as the processing aid.

[0079] When the composition for a transmission belt contains a processing aid, the content of the processing aid is usually 10 parts by mass or less, preferably 8.0 parts by mass or less, more preferably 6.0 parts by mass or less, even more preferably 4.0 parts by mass or less, and particularly preferably 2.0 parts by mass or less, per 100 parts by mass of the total of the copolymer (A) and the copolymer (B).

[0080] Activator Examples of activators include amines such as di-n-butylamine, dicyclohexylamine, and monoethanolamine; activators such as diethylene glycol, polyethylene glycol, lecithin, and triaryl ether mellate, zinc compounds of aliphatic or aromatic carboxylic acids; zinc peroxide preparations; octadecyltrimethylammonium bromide, synthetic hydrotalcites, and special quaternary ammonium compounds.

[0081] When the composition for a transmission belt contains an activator, the content of the activator is usually 0.2 to 10 parts by mass, preferably 0.3 to 5 parts by mass, per 100 parts by mass of the total of the copolymer (A) and the copolymer (B).

[0082] Moisture absorbent Examples of moisture absorbents include calcium oxide, silica gel, sodium sulfate, molecular sieves, zeolite, and white carbon.

[0083] When the composition for a transmission belt contains a moisture absorbent, the content of the moisture absorbent is usually 0.5 to 15 parts by mass, and preferably 1.0 to 12 parts by mass, per 100 parts by mass of the total of the copolymer (A) and the copolymer (B).

[0084] Other Polymers The composition for a power transmission belt may further contain a polymer other than the copolymer (A) and the copolymer (B) (hereinafter, also referred to as "another polymer").

[0085] Other polymers that require crosslinking include rubbers such as natural rubber, isoprene rubber, butadiene rubber, styrene-butadiene rubber, chloroprene rubber, nitrile rubber, butyl rubber, acrylic rubber, silicone rubber, fluororubber, and urethane rubber.

[0086] Other polymers that do not require crosslinking include elastomers such as styrene-butadiene block copolymers (SBS), styrene-based thermoplastic elastomers (TPS) such as polystyrene-poly(ethylene-butylene)-polystyrene (SEBS) and polystyrene-poly(ethylene-propylene)-polystyrene (SEPS), olefin-based thermoplastic elastomers (TPO), vinyl chloride-based elastomers (TPVC), ester-based thermoplastic elastomers (TPC), amide-based thermoplastic elastomers (TPA), urethane-based thermoplastic elastomers (TPU), and other thermoplastic elastomers (TPZ).

[0087] The composition for a power transmission belt may contain an alkylphenol-acetaldehyde resin. Alkylphenol-acetaldehyde resins are generally resins made of a compound represented by the following formula (X): Examples of alkylphenols having an alkyl group or alicyclic alkyl group having 3 to 12 carbon atoms in the following formula (X) include p-isopropylphenol, p-tert-butylphenol, p-tert-octylphenol, p-nonylphenol, p-dodecylphenol, and p-cyclohexylphenol.

[0088] [ka] (In formula (X), n is 1 or 2, and R is an alkyl group or an alicyclic alkyl group having 3 to 12 carbon atoms.)

[0089] Commercially available alkylphenol-acetaldehyde resins include, for example, TACKIROL 160 (manufactured by Taoka Kogyo Co., Ltd.) and TACKIROL EP-30 (manufactured by Taoka Kogyo Co., Ltd.).

[0090] When the composition for a transmission belt contains another polymer, the content of the other polymer is usually 100 parts by mass or less, preferably 80 parts by mass or less, more preferably 50 parts by mass or less, even more preferably 20 parts by mass or less, and particularly preferably 10 parts by mass or less, based on 100 parts by mass in total of the copolymer (A) and the copolymer (B).

[0091] <Preparation of Composition> The composition for a transmission belt can be prepared by kneading the copolymer (A), the copolymer (B), zinc oxide (C), the cyclohexylamine salt of 2-mercaptobenzothiazole (D), the sulfur compound-based crosslinking agent (E), and other components that are blended as necessary, at a desired temperature using a kneading machine such as a mixer, a kneader, or a roll.

[0092] One embodiment of the composition for a transmission belt is prepared, for example, as follows: Copolymer (A), copolymer (B), zinc oxide (C), and other components as necessary are charged into a kneader and kneaded uniformly under predetermined heating conditions (e.g., 80 to 200°C for 3 to 30 minutes) (kneading A). In kneading A, a sulfur compound-based crosslinking agent (E) or the like that crosslinks copolymer (A) and copolymer (B) when heated to the heating temperature for kneading A is not charged. As the copolymer (A), an oil-extended product containing the copolymer (A) and an oil-extending component may be added, or the copolymer (A) may be added alone. Oil extending components include, for example, paraffin-based processing oils and hydrocarbon-based synthetic oils.

[0093] The temperature of the mixture kneaded in kneading A is then lowered to below the crosslinking temperature of the sulfur compound-based crosslinking agent (E) (for example, 130°C or lower), and then the sulfur compound-based crosslinking agent (E) and the cyclohexylamine salt of 2-mercaptobenzothiazole (D), etc., which were not added in kneading A, are added to the mixture, and the mixture is further kneaded and homogenized under specified heating conditions (for example, at a roll temperature of 30 to 80°C for 1 to 30 minutes) (kneading B), to obtain the composition for a power transmission belt. The composition for a power transmission belt has excellent adhesion to a core material.

[0094] [Laminate and power transmission belt] The laminate according to the present invention is a laminate including a layer [I] containing the composition for a transmission belt or a cross-linked product thereof, and a layer [II] containing a diene rubber or a cross-linked product thereof, which is in contact with the layer [I].

[0095] The layer [I] can be formed from the composition for a transmission belt, and can be molded by a thermoforming method such as extrusion molding, injection molding, press molding, calendar molding, transfer molding, and foam molding. When the composition for a transmission belt is crosslinked, the crosslinking temperature is usually 140° C. or higher, preferably 150 to 220° C., and more preferably 160 to 200° C. This crosslinking reaction can be carried out in air.

[0096] The composition for a power transmission belt has high adhesive strength suitable for molding processability and is excellent in belt processability. In addition, by using the composition for a power transmission belt, a component member for a power transmission belt having high rubber elasticity, abrasion resistance, heat resistance, and cold resistance can be produced. The layer [I] can be suitably used as a constituent member of a power transmission belt.

[0097] The layer [II] can be formed from a diene rubber, and can be molded by a thermoforming method such as extrusion molding, injection molding, press molding, calendar molding, transfer molding, and foam molding.

[0098] Diene rubbers are rubbers having double bonds in the polymer main chain, and examples thereof include NR, IR, BR, SBR, NBR, CR and IIR. These may be used alone or in combination of two or more.

[0099] When the layer [II] is a crosslinked product of a diene rubber, a crosslinking agent that is conventionally used for diene rubbers can be used as the crosslinking agent for the diene rubber. When the diene rubber is crosslinked, the crosslinking temperature is usually 140° C. or higher, preferably 150 to 220° C., and more preferably 160 to 200° C. The crosslinking reaction can be carried out in air.

[0100] Further, the laminate of the present invention is preferably a laminate obtained by laminating a layer [I] containing the composition for a transmission belt containing the crosslinking agent (i.e., an uncrosslinked composition) and a layer [II] containing the diene-based rubber (i.e., an uncrosslinked rubber) so as to be in contact with each other, and then heat-treating the laminate at a crosslinking temperature.

[0101] In such a laminate, crosslinking occurs between the rubber components (the copolymer (A) and the copolymer (B)) contained in the composition for a transmission belt and the diene rubber, and therefore it is considered that the layer [I] exhibits particularly excellent adhesion to the layer [II].

[0102] The crosslinking temperature is usually 140° C. or higher, preferably 150 to 220° C., and more preferably 160 to 200° C. In addition, the heat treatment can be carried out in air.

[0103] The power transmission belt of the present invention has the above-mentioned laminate of the present invention. Examples of the transmission belt of the present invention include friction transmission belts such as V-belts and V-ribbed belts, and meshing transmission belts such as timing belts. Examples of the transmission belt include automobile transmission belts, motorcycle transmission belts, and general industrial machine transmission belts. Examples of the V-belt include wrapped belts and raw edge belts.

[0104] One embodiment of the power transmission belt may have, for example, an adhesive rubber part in which a core wire is embedded, and may further have a bottom rubber part formed on the lower surface of the adhesive rubber part. The power transmission belt may have an upper canvas formed on the adhesive rubber part and / or a lower canvas formed under the bottom rubber part, as necessary. A rubber layer for adhering the canvas may be interposed between the adhesive rubber part and the upper canvas, and between the bottom rubber part and the lower canvas, respectively.

[0105] The composition for a transmission belt is preferably used for forming, for example, a rubber layer for adhering a canvas. Specifically, a crosslinked molded article formed from the composition for a transmission belt is preferably used as the rubber layer for adhering a canvas.

[0106] The rubber used to form the adhesive rubber portion and / or the bottom rubber portion is preferably the diene rubber described above. The core wire, which is a tensile member of the power transmission belt, extends in the longitudinal direction of the belt in the bonded rubber portion. The core wire may be, for example, a polyester cord. The bonded rubber portion surrounds the core wire and is bonded to the core wire.

[0107] In another embodiment, for example, the composition for a transmission belt is disposed around a core wire and crosslinked, thereby forming an adhered rubber portion adhered to the core wire. Examples of canvas include canvas made of cotton, blends of cotton and polyester, and blends of cotton and polyamide. EXAMPLES

[0108] The present invention will be described in more detail below based on examples, but the present invention is not limited to these examples. [Measurement method ~Physical properties of ethylene-α-olefin-non-conjugated polyene copolymer (A) etc.~] The physical properties of the ethylene-α-olefin-non-conjugated polyene copolymer (A) and the ethylene-α-olefin-non-conjugated polyene copolymer (B) were measured as follows.

[0109] <Molar amounts of structural units derived from ethylene, structural units derived from α-olefin, and structural units derived from non-conjugated polyene> The molar amounts are 1 determined by intensity measurement using an H-NMR spectrometer. Details of the measurement conditions are described in International Publication No. 2015 / 122415.

[0110] <Mooney viscosity> The Mooney viscosities ML(1+4) 125°C and ML(1+4) 100°C were measured in accordance with JIS K 6300 (1994) using a Mooney viscometer (Model SMV-301 manufactured by Shimadzu Corporation).

[0111] Using o-dichlorobenzene-d4 / benzene-d6 (4 / 1 [v / v]) as the measurement solvent and a measurement temperature of 120°C, 13 a 13C-NMR spectrum (100 MHz, ECX400P manufactured by JEOL Ltd.) was measured, and the B value was calculated based on the following formula (ia) for copolymer (A) and based on the following formula (ib) for copolymer (B). B value = ([EB] + 2[Y]) / {2 × [E] × ([B] + [Y])} ··· (ia) B value = [EP] / (2[E] × [P]) ··· (ib) (The meanings of [E], [B], [P], [Y], [EB], and [EP] are as described above.)

[0112] [Measurement method ~ Physical properties of compositions, etc. ~] The physical properties of the compositions, etc. of the examples and comparative examples were measured as follows.

[0113] <Viscosity test> In accordance with JIS K 6300 (1994), the Mooney viscosity ML(1+4) 100°C was measured using a Mooney viscometer (Model SMV-301 manufactured by Shimadzu Corporation).

[0114] <Vulcanization rate test> Using MDR2000P (manufactured by ALPHATECHNOLOGIES) as a measuring device, the torque change obtained under the conditions of a constant temperature and a constant shear rate in the compound 2 described later was measured under the measurement conditions of a temperature of 155°C and a time of 30 minutes, and the difference between the minimum torque value S'min and the maximum torque value S'max (S'max-S'min), the time (TS1) from when the torque of the measured sample reaches the minimum torque value S'min until the torque increases by 1 [dNm], and the time (tc90) from when the torque of the measured sample reaches the minimum torque value S'min until it reaches 90% of the value when the minimum torque value S'min is 0% and the maximum torque value S'max is 100% were obtained. The smaller the tc90, the higher the vulcanization speed (crosslinking speed).

[0115] <Hardness test (Durometer-A)> The flat portions of the 2 mm thick crosslinked sheets produced in the Examples and the like were stacked to form a 12 mm thick sheet, and the hardness (JIS-A) was measured in accordance with JIS K 6253 (2012).

[0116] <Tensile test: modulus, tensile stress at break, tensile elongation at break> A 2 mm-thick crosslinked sheet prepared in the Examples was punched out to prepare a No. 3 dumbbell test piece described in JIS K 6251 (1993). Using this test piece, a tensile test was performed according to the method specified in JIS K 6251, section 3, at a measurement temperature of 25°C and a tensile speed of 500 mm / min, and the tensile stress (25% modulus (M25) to 300% modulus (M300)), tensile stress at break (TB), and tensile elongation at break (EB) were measured.

[0117] <Peel test> In accordance with JIS K 6854-3 (1999), a T-peel test was carried out at a measurement temperature of 23.0°C, a test speed of 200 mm / min, and a test piece width of 25.0 mm, and the peel strength (the force required to peel off the vulcanized adherend) was measured.

[0118] [Production Example 1] <Production of ethylene-α-olefin-non-conjugated polyene copolymer (A-1)> Ethylene-1-butene-ENB copolymer (copolymer (A-1)) was obtained according to the description of [Synthesis Example C1] in WO 2015 / 122415, while adjusting the amounts of ethylene, 1-butene, and 5-ethylidene-2-norbornene (ENB) fed to the polymerization reactor. The composition and physical properties of copolymer (A-1) are shown in Table 1.

[0119] [Production Example 2] <Production of ethylene-α-olefin-non-conjugated polyene copolymer (A-2)> Ethylene-1-butene-ENB copolymer (copolymer (A-2)) was obtained according to the description of [Synthesis Example C1] in WO 2015 / 122415, while adjusting the amounts of ethylene, 1-butene, and 5-ethylidene-2-norbornene (ENB) fed to the polymerization reactor. The composition and physical properties of copolymer (A-2) are shown in Table 1. An oil-extended product (A-2) containing a copolymer (A-2) and an oil-extending component (paraffin-based process oil) was used when producing the compositions for transmission belts of Example 1 and Comparative Examples 1 to 3. The content of the oil-extending component in the oil-extended product (A-2) was 23% by mass relative to 100% by mass of the oil-extended product (A-2).

[0120] [Production Example 3] <Production of ethylene-α-olefin-non-conjugated polyene copolymer (B-1)> According to the description of [Production Example 1] in JP 2014-208740 A, and by adjusting the amounts of ethylene, 1-butene, 5-ethylidene-2-norbornene (ENB) and 5-vinyl-2-norbornene (VNB) fed to the polymerization reactor, an ethylene-propylene-ENB-VNB copolymer (copolymer (B-1)) was obtained. The composition and physical properties of copolymer (B-1) are shown in Table 1.

[0121] [Table 1]

[0122] [Production Example 4] <Production of Adherend (Layer (II))> Details of the raw materials used to prepare the adherends are shown in Table 2 below.

[0123] [Table 2]

[0124] In the first stage, 60 parts by mass of NR and 40 parts by mass of SBR were masticated for 1 minute using a BB-4 type Banbury mixer (manufactured by Kobe Steel, Ltd.), and then 5 parts by mass of ZnO#1, 1 part by mass of stearic acid, 70 parts by mass of carbon black (Asahi #60UG, manufactured by Asahi Carbon Co., Ltd.), and 3 parts by mass of Nocrac 224 were added and kneaded for 3 minutes at 110°C. Thereafter, the ram was raised and cleaned, and kneading was further carried out for 2 minutes and discharged at 125°C to obtain compound a of the first stage. The kneading conditions for preparing compound a were rotor rotation speed of 40 rpm and floating weight pressure of 3 kgf / cm. 2 It was.

[0125] Next, in the second stage, after confirming that the temperature of compound a had reached 40°C, 3.5 parts by mass of sulfur, 1.2 parts by mass of a vulcanization accelerator (Suncerer CM, manufactured by Sanshin Chemical Industry Co., Ltd.), and 0.2 parts by mass of a vulcanization accelerator (Suncerer DM, manufactured by Sanshin Chemical Industry Co., Ltd.) were added to compound a and kneaded using an 8-inch roll, and the mixture was dispensed for a kneading time of 8 minutes to obtain compound b. The kneading conditions for preparing compound b were roll temperature front roll / rear roll = 50°C / 50°C, roll peripheral speed front roll / rear roll = 18 rpm / 15 rpm, and roll gap 3 mm.

[0126] Next, the compound b was pressed using a press molding machine at 80° C. for 2 minutes to produce an adherend (layer [II]) having a thickness of 1 mm.

[0127] [Example 1] <Composition> In the first step, 68 parts by mass of copolymer (A-1), 19.5 parts by mass of oil-extended product (A-2) (15 parts by mass of copolymer (A-2)), and 17 parts by mass of copolymer (B-1) were masticated for 1 minute using a BB-4 type Banbury mixer (manufactured by Kobe Steel, Ltd.), and then 5 parts by mass of zinc oxide (ZnO#1, manufactured by Hakusui Tech Co., Ltd.), 1 part by mass of stearic acid, and an antioxidant (Nocrac 224, manufactured by Ouchi Shinko Chemical Industry Co., Ltd.) were added thereto. 2 parts by mass of antioxidant (Sandant MB, Sanshin Chemical Industry Co., Ltd.), 2 parts by mass of carbon black (Seest G-SO, Tokai Carbon Co., Ltd.), 80 parts by mass of paraffinic process oil (Diana Process Oil PW-380, Idemitsu Kosan Co., Ltd.), and 7.5 parts by mass of alkylphenol-acetaldehyde resin (Tackirol EP-30, Taoka Kogyo Co., Ltd.) were added and kneaded for 2 minutes at 120°C. The ram was then raised and cleaned, and kneaded for a further 2 minutes and discharged at 144°C to obtain first-stage compound 1.

[0128] The mixing conditions for compound 1 were: rotor speed 40 rpm, floating weight pressure 3 kgf / cm 2 It was. Next, in the second step, after confirming that the temperature of Compound 1 had reached 40°C, 2 parts by mass of sulfur, 1 part by mass of a vulcanization accelerator (Suncellar CM, manufactured by Sanshin Chemical Industry Co., Ltd.), 0.6 parts by mass of a vulcanization accelerator (Suncellar BZ, manufactured by Sanshin Chemical Industry Co., Ltd.), 0.3 parts by mass of a vulcanization accelerator (Suncellar TT, manufactured by Sanshin Chemical Industry Co., Ltd.), and 1.5 parts by mass of a vulcanization accelerator (Suncellar HM, manufactured by Sanshin Chemical Industry Co., Ltd.) were added to Compound 1 using an 8-inch roll and kneaded, and then dispensed for a kneading time of 8 minutes to obtain Compound 2.

[0129] The kneading conditions for preparing Compound 2 were as follows: roll temperature front roll / rear roll = 50°C / 50°C, roll peripheral speed front roll / rear roll = 18 rpm / 15 rpm, and roll gap 3 mm.

[0130] Compound 2 was pressed at 80°C for 2 minutes using a press molding machine to produce an unvulcanized sheet having a thickness of 1 mm. Compound 2 was also pressed at 155°C for 15 minutes using a press molding machine to produce a crosslinked sheet having a thickness of 2 mm. The unvulcanized sheet and crosslinked sheet obtained were subjected to various measurements. The results are shown in Table 4.

[0131] <Laminate> The resulting unvulcanized sheet having a thickness of 1 mm was laminated onto the adherend prepared in Production Example 4 and pressed at 160° C. for 10 minutes using a press molding machine to prepare a laminate having a thickness of 2 mm. The obtained laminate was subjected to a peel test, and the results are shown in Table 4.

[0132] [Comparative Examples 1 to 3] The same procedure was followed as in Example 1, but based on the composition and cure system set out in Table 4. The materials used in the examples and comparative examples are shown in Table 3 below.

[0133] [Table 3]

[0134] [Table 4]

Claims

1. (B) an ethylene / α-olefin / non-conjugated polyene copolymer comprising a structural unit [b1] derived from ethylene, a structural unit [b2] derived from an α-olefin having 3 to 20 carbon atoms, a structural unit [b3] derived from a non-conjugated polyene containing only one partial structure represented by the following general formula (I) or (II) in the molecule, and a structural unit [b4] derived from a non-conjugated polyene containing a total of two or more partial structures represented by the following general formula (I) or (II) in the molecule; (A) an ethylene / α-olefin / non-conjugated polyene copolymer comprising a structural unit [a1] derived from ethylene, a structural unit [a2] derived from an α-olefin having 4 to 20 carbon atoms, and a structural unit [a3] derived from a non-conjugated polyene (excluding the copolymer (B)); (C) zinc oxide, (D) the cyclohexylamine salt of 2-mercaptobenzothiazole, and (E) Sulfur compound-based crosslinking agent A composition for a transmission belt comprising: 【Chemistry 1】

2. The composition for a transmission belt according to claim 1, wherein the copolymer (B) satisfies the following requirements (b-1) and (b-2): Requirement (b-1): The molar ratio ([b1] / [b2]) of the structural unit [b1] derived from ethylene to the structural unit [b2] derived from an α-olefin having 3 to 20 carbon atoms is 50 / 50 to 75 / 25. Requirement (b-2): The B value represented by the following formula (ib) is 1.05 or less. B value = [EP] / (2 [E] x [P]) ... (ib) (In formula (ib), [E] and [P] respectively represent the molar fraction of the structural unit [b1] derived from the ethylene and the molar fraction of the structural unit [b2] derived from the α-olefin having 3 to 20 carbon atoms, and [EP] represents the dyad chain fraction of ethylene / α-olefin having 3 to 20 carbon atoms.)

3. 3. A laminate comprising a layer [I] containing the composition for a transmission belt or a crosslinked product thereof according to claim 1 or 2, and a layer [II] containing a diene rubber or a crosslinked product thereof, the layer [I] being in contact with the layer [I].

4. A power transmission belt comprising the laminate according to claim 3.

Citation Information

Patent Citations

  • Short fiber reinforced elastomer composition for transmission belt and transmission belt

    JP2001310951A

  • Friction transmission belt

    JP2012215212A

  • Rubber composition for transmission belt

    JP2016044198A

  • Transmission belt composition, and use thereof transmission belt

    JP2021161358A

  • Ethylene / Α-olefin / non-conjugated polyene copolymer, use therefor, and manufacturing method therefor

    WO2015122415A1

Cited By

  • Crosslinked rubber composition and power transmission belt using the same

    JP7932000B2

  • JPWO2026028601A1

  • Crosslinked rubber composition and transmission belt using same

    WO2026028601A1